Double skin façade (DSF) technologies for UK office refurbishments: A systemic matchmaking practice. Issue 4 (9th November 2015) - Pomponi, Francesco; Piroozfar, Poorang A. E.
Abstract : Purpose: – The purpose of this paper is to establish how UK offices and double skin façade (DSF) technologies can be best matched for refurbishment purposes. Design/methodology/approach: – This research uses a mixed methodology including primary and secondary data collection, analysis and interpolation through document analysis, comprehensive critical literature review, and case study approach. Findings: – In total, 22 benchmarks have been developed to represent 75 per cent of the existing office stock in the UK. Through a comparison with 36 case studies of European buildings refurbished with DSFs, two benchmarks showed to be most suitable for a DSF refurbishment and most appropriate configurations for a successful DSF refurbishment have been identified. Findings have been also checked against a large sample of DSF buildings in the UK. Research limitations/implications: – The benchmarks delivered in this study can be developed further into parametric models, where variations can be obtained by changing the parameters provided. A follow-up study can be designed to help define the exact share of existing stock represented by each benchmark and to foster research where a more typological or statistical approach might be intended. Practical implications: – Findings from this research can be of practical use to academics and practitioners alike involved in research related to office refurbishments, DSFs, and the UK existing office stock. The design for this research can also be adapted to similar studies on its own or further developed to suit different contexts. Social implications: – Improvements to existing buildings can preserve established communities, with a clear social advantage. Originality/value: – This paper represents the first attempt to systemically shed light on how existing UK offices and DSF technologies can be best matched in refurbishments. The benchmarks developed, the DSF case studies, and guidelines for suitable DSF technologies in UK office refurbishments represent the original contribution of this research.